PTU-195 Six years of laparoscopic Nissen's fundoplication, was it worth it? An audit of 100 patients. (28th May 2012) - Martin, L; Stavrou, M; El Madani, F; Gupta, S
Abstract : Introduction: Nissen's fundoplication for gastro-oesophageal reflux disease provides good long term control of acid reflux but is often not without unwanted side-effects. We investigated long term outcome of Nissen's fundoplication at our centre. Methods: Study group included 100 patients who underwent Nissen's fundoplication from 2005 to 2011 at our unit. Pre-operative demographics, symptom profile, investigations and operative data were reviewed. Symptoms after surgery (heartburn, dysphagia, bloating and excessive flatus), antacid usage and patient satisfaction were assessed using a follow-up questionnaire. Results: Average patient age was 47.5 years (19–79 years) with male to female ratio of 57:43. Majority of patients were obese or overweight (79%). Average follow-up was 39 months (3–80 months). Main symptoms included acid reflux (99%), volume reflux (56%) and nocturnal and postural reflux (45%). Gastroscopy revealed hiatus hernia 92%, reflux oesophagitis 71% and Barrett's oesophagus 11%. pH studies and manometry were undertaken in 90% and 93% of patients respectively. Mean acid exposure time was 16.2% (median 13%, range 1.4%–86%), mean symptom index was 79.25% (median 91%, range 1–100%) and mean Demeester score was 50.51 (median 30, range 4.7–291). Lower oesophageal sphincter pressure was normal in 54%, low in 37% and high in 9% of patients with complete relaxation in 91%. No patient had significant oesophageal dysmotility. No routine follow-up pH studies were undertaken. A primary crural repair with 360° short and floppy fundal wrap was constructed on all the patients. Hiatus was prosthetically reinforced on 17 patients (collagen patch 12, mesh 5). Conversion to open surgery was 2% (splenic bleed, difficult anatomy). Four patients required further surgery during follow-up period (severe dysphagia 2, excessive flatus 1, herniation through the wrap 1). Questionnaire responses from 96/100 patients were analysed (postal 56, telephonic 22, clinic review 18). Most patients (81%) were happy to have undergone surgery and would recommend this procedure to a friend (79%). A total of 58 patients (60%) were not on any anti-acid drugs, however 17 patients (18%) were on regular PPIs. Frequencies of post-operative symptoms are detailed below. Overall outcome was described by patients as excellent 43%, good 38%, fair 11% and poor 8%. Conclusion: Majority of patients undergoing Laparoscopic Nissen's fundoplication had good long term control of acid reflux and were happy with their decision to undergo surgery. Wind related side effects are a significant cause for dissatisfaction and must be emphasised during decision making for surgery. Competing interests: None declared.